-х2 ‹ -2,7х
(х2- х в квадрате)

NikaAs1 NikaAs1    1   23.04.2020 17:16    0

Ответы
kozackilya1 kozackilya1  13.10.2020 19:03

2х^2+х+7=-х^2+5х+(-2-х^2)

-2х^2+х+7= -х^2+5х-2-х^2

-2х^2+х+7=-2х^2+5х-2

-2х^2+х+7+2х^2-5х+2=0

-4х+9=0

-4х=-9

х=-9/-4

х=2,25

ответ:2,25

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Hhjkklknbggfddxxg Hhjkklknbggfddxxg  13.10.2020 19:03

Объяснение:

-х2 ‹ -2,7х

-х2 +2,7х‹0

х2-2,7х>0

х(х-2,7)>0

х>0          х-2,7>0

               х>2,7

ответ:х>0; х>2,7

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра